Concomitant Transsphenoidal Approach to the Anterior Skull Base and Endoscopic Sinus Surgery in Patients with Chronic Rhinosinusitis - Schaberg, Madeleine R.; Shah, Gopi B.; Evans, James J.; Rosen, Marc R. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objectives To describe outcomes of endoscopic resection of sellar tumors with concomitant endoscopic sinus surgery for patients with chronic rhinosinusitis (CRS).Design Retrospective chart review.Setting Tertiary care medical center.Participants Patients who underwent endoscopic transsphenoidal surgery for excision of anterior skull base lesions and simultaneous functional endoscopic sinus surgery (FESS) for CRS between January 2006 and January 2011 by senior authors (MRR and JJE).Main Outcomes Measured Short- and long-term postoperative complications.Results Fourteen patients were identified. Average follow-up was 27 months. All patients had preoperative symptoms consistent with CRS. No patients were treated with preoperative antibiotics. Surgical pathology revealed chronic sinusitis in all specimens. Pathology of the intracranial lesions included 11 pituitary macroadenomas, one craniopharyngioma, one chondrosarcoma, and one cholesterol granuloma. Short-term postoperative morbidities included a sphenoid polyp, one adhesion, and one case of pharyngitis. Long-term outcomes included one frontoethmoidal mucocele, one recurrence of nasal polyps, and three cases of acute sinusitis. There were no intracranial complications for the entire follow-up period.Conclusions Transsphenoidal surgery can safely be performed in the setting of CRS without increased risk of intracranial complications.
Keywords: endoscopic endonasal transsphenoidal approach; anterior cranial base; nasal complications; pituitary; endoscopic sinus surgery